Nature-Positive Agriculture—A way forward towards resilient agrifood systems - Kaushal, Manoj; Atieno, Mary; Odjo, Sylvanus; Baijukya, Frederick; Gebrehawaryat, Yosef; Fadda, Carlo (MDPI, 2025)
Current food production systems rely heavily on resource-poor small-scale farmers in the global south. Concomitantly, the agrifood systems are exacerbated by various a/biotic challenges, including low-input agriculture and climate crisis. The recent global food crisis further escalates the production and consumption challenges in the global market. With these challenges, coordinated efforts to address the world’s agrifood systems challenges have never been more urgent than now. This includes the implementation of deeply interconnected activities of food, land, and water systems and relationships among producers and consumers that operate across political boundaries. Nature-positive agriculture represents interventions both at the farm and landscape level that include a systems approach for the management of diverse issues across the land-water-food nexus. In the present article, we focus on the history of traditional farming and how it evolved into today’s nature-positive agriculture, including its limitations and opportunities. The review also explains the most impactful indicators for successful nature-positive agriculture, including sustainable management of soil, crops, seeds, pests, and mixed farming systems, including forages and livestock. Finally, the review explains the dynamics of nature-positive agriculture in the context of small-scale farming systems and how multilateral organizations like the CGIAR are converting this into transformative actions and impact. To address the climate crisis, CGIAR established the paradigm of nature-positive solutions as part of its research and development efforts aimed at transforming food, land, and water systems into more resilient and sustainable pathways.